Revolutionizing Africa's carbon footprint through innovative technology dissemination strategies for greenhouse gas emission reduction: an MCDM approach - Tafuteni Chusi; Su Qian; Jakub Więckowski; Mouhamed Bayane Bouraima; Yanjun Qiu (Journal of Fuzzy Extension and Applications)
In recent years, the urgency to tackle climate change and transition to sustainable energy sources has intensified. Africa, rich in Renewable Energy (RE) potential, is uniquely positioned to lead this global movement. However, the dissemination of innovative technologies for Greenhouse Gas (GHG) emission reduction is impeded by various challenges. This study identifies seven strategies through expert consultations and literature reviews and employs the Stepwise Weight Assessment Ratio Analysis (SWARA) within an Interval-Valued Intuitionistic Fuzzy (IVIF) framework to assess their relative importance. Key findings highlight that building robust RE infrastructure, leveraging incentives for adoption, fostering international knowledge partnerships, and enhancing capacity-building efforts are the most effective strategies. To strengthen the analysis, a comparative study with two other Multi-Criteria Decision-Making (MCDM) methods is conducted. The study recommends investing in solar and wind energy projects, offering subsidies and tax incentives to attract investment, and establishing a solid policy framework to encourage collaboration. Furthermore, enhancing vocational training and partnering with educational institutions is essential for developing a skilled workforce and ensuring long-term sustainability.